2020
DOI: 10.3389/fmicb.2020.00564
|View full text |Cite
|
Sign up to set email alerts
|

Taking Control: Campylobacter jejuni Binding to Fibronectin Sets the Stage for Cellular Adherence and Invasion

Abstract: Campylobacter jejuni, a foodborne pathogen, is one of the most common bacterial causes of gastroenteritis in the world. Undercooked poultry, raw (unpasteurized) dairy products, untreated water, and contaminated produce are the most common sources associated with infection. C. jejuni establishes a niche in the gut by adhering to and invading epithelial cells, which results in diarrhea with blood and mucus in the stool. The process of colonization is mediated, in part, by surface-exposed molecules (adhesins) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 123 publications
1
43
0
Order By: Relevance
“…This is consistent with our result that a combination of adhesin mutant bacteria and the use of chloramphenicol led to the highest restoration of individual cell motility. The requirement of both adhesins and effector proteins for host cell changes is also consistent with the established model of C. jejuni invasion (Konkel et al, 2020;Ó Cróinín & Backert, 2012).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is consistent with our result that a combination of adhesin mutant bacteria and the use of chloramphenicol led to the highest restoration of individual cell motility. The requirement of both adhesins and effector proteins for host cell changes is also consistent with the established model of C. jejuni invasion (Konkel et al, 2020;Ó Cróinín & Backert, 2012).…”
Section: Discussionsupporting
confidence: 83%
“…We have shown that C. jejuni manipulates the size, structure, and composition of focal adhesions. Based on previous research connecting C. jejuni adhesins to focal adhesion components (Konkel, Talukdar, Negretti, & Klappenbach, 2020;Krause-Gruszczynska et al, 2011;Monteville et al, 2003), we hypothesized that the CadF and FlpA adhesins could be responsible for driving the observed changes in the focal adhesion. First, we tested if the CadF and FlpA adhesins were required for signaling changes in the focal adhesion by examining paxillin phosphorylation.…”
Section: Mechanism Of C Jejuni Focal Adhesion Manipulationmentioning
confidence: 99%
“…C. jejuni adhesins seem to have alternate primary functions, yet some can target the same host receptor such as fibronectin. Once C. jejuni adheres to fibronectin on the basolateral side of human IECs, it is preceded by secondary steps that orchestrate cellular invasion ( Konkel et al., 2020 ). The most highly investigated adhesins in C. jejuni that exist almost in mutually exclusive fashion are Campylobacter adhesion to fibronectin (CadF) and fibronectin-like protein A (FlpA).…”
Section: Jejuni Putative Adhesinsmentioning
confidence: 99%
“…C. jejuni adhesins (CadF and FlpA) are highly conserved among C. jejuni strains. CadF and FlpA proteins are important for C. jejuni adherence to human IECs and colonization of chickens ( Konkel et al., 2020 ). A C. jejuni cadF mutant displays reduced ability to adhere to human IECs and chicken hepatoma cell line, LMH cells.…”
Section: Jejuni Putative Adhesinsmentioning
confidence: 99%
“…The Staphylococcus aureus proteins FnBP-A and FnBP-B were some of the first FnBPs described to indirectly interface with integrin receptors [ 210 ]. Other FnBPs include Streptococcus pyogenes SfbI/Protein F1 [ 208 ] as well as the well-characterized CadF and FlpA made by Campylobacter jejuni [ 204 ]. The gastrointestinal pathogen C. jejuni colonizes polarized intestinal epithelial cells, and this attachment requires fibronectin and CadF.…”
Section: Pathogenic Microbes Utilize “Outside–in” and “Inside–out”mentioning
confidence: 99%